Wildfire smoke in the lower stratosphere identified by in situ CO observations - Hooghiem, Joram J. D.; Popa, Maria Elena; Röckmann, Thomas; Grooß, Jens-Uwe; Tritscher, Ines; Müller, Rolf; Kivi, Rigel; Chen, Huilin (Atmospheric Chemistry and Physics, 2020)
Wildfires emit large quantities of aerosols and trace gases, which occasionally reach the lower stratosphere. In August 2017, several pyro-cumulonimbus events injected a large amount of smoke into the stratosphere, observed by lidar and satellites. Satellite observations are in general the main method of detecting these events since in situ aircraft- or balloon-based measurements of atmospheric composition at higher altitudes are not made frequently enough. This work presents accidental balloon-borne trace gas observations of wildfire smoke in the lower stratosphere, identified by enhanced CO mole fractions at approximately 13.6 km. In addition to CO mole fractions, CO2 mole fractions and isotopic composition of CO (δ13C and δ18O) have been measured in air samples, from both the wildfire plume and background, collected using an AirCore and a lightweight stratospheric air sampler (LISA) flown on a weather balloon from Sodankylä (4–7 September 2017; 67.37∘ N, 26.63∘ E; 179 m a.m.s.l.), Finland. The greenhouse gas enhancement ratio (ΔCO:ΔCO2) and the isotopic signature based on δ13C(CO) and δ18O(CO) independently identify wildfire emissions as the source of the stratospheric CO enhancement. Back-trajectory analysis was performed with the Chemical Lagrangian Model of the Stratosphere (CLaMS), tracing the smoke's origin to wildfires in British Columbia with an injection date of 12 August 2017. The trajectories are corrected for vertical displacement due to heating of the wildfire aerosols, by observations made by the Cloud-Aerosol Lidar with Orthogonal Polarization (CALIOP) instrument. Knowledge of the age of the smoke allowed for a correction of the enhancement ratio, ΔCO:ΔCO2, for the chemical removal of CO by OH. The stable isotope observations were used to estimate the amount of tropospheric air in the plume at the time of observation to be about 45±21 %. Finally, the plume extended over 1 km in altitude, as inferred from the observations.